(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2023)
The article deals with the phenomenon of homonymy and their classification. This article includes information of homonymy and characteristics, the main reasons for the appearance of homonymys in English language. Homonymy is quite frequent and difficult concept in linguistics, as well as homonymys are able to enrich and decorate any language